Review on the Role of Geographic Information System and Remote Sensing for Watershed Management - Barena Adare (International Journal of Scientific Research in Civil Engineering, 2021)
The objective of many  water resource and watershed studies include irrigation performance, ground water management, rain fall estimation, run off for casting evaluating, waste disposal, disaster monitoring, watershed segmentation, infiltration monitoring characterizing of terrain slop and aspect ,catchments configuration and routing of the flow  of water , wet land management . Concerning these variables has been difficult to do from paper maps and aerial photographs. GIS and remote sensing technologies are different strengths bring to water resource and watershed monitoring GIS allows for improved data base organization and storage. GIS and RS have thus become important tools for evaluation of the physical attributes of water and land recourse in many parts of the world and provides an unique opportunity towards comprehensive monitoring of water resource and watershed dynamics characteristic.  There are different case studies on rainfall estimation, run off fore casting, irrigation potential evolution, surface and ground water management, wasted disposal, disaster monitoring, wet land monitoring and watershed management have proved beyond doubt that integration of remote sensing and conventional approaches significantly decrease the cost and time involved as well as improve the steadfastness.
Keywords: Decision Support System; Geographical Information Systems; Global